ANALISIS PENGARUH KARAKTERISTIK PEKERJAAN TERHADAP KEPUASAN KERJA (Studi empiris pada pedagang Mie Ayam di Kecamatan Tahunan) - Much Imron (Jurnal Dinamika Ekonomi & Bisnis, 2006)
AbstractThis research aim to analyse influence of work characteristic which consist of skilled variation, work autonomy and duty identity to job satisfaction its research object is merchant of chicken noodles in Tahunan Jepara. Population this research is all merchant of chicken noodles counted 134 people, while amount of taken sampet counted 100 one taken wnh random sampling techniques. Data type used is primary and secondary data, collected with documentation and questioner. Technique analyse multiple regression used to test influence of independent variable (skilled variation, work autonomy and duty identity) to dependent variable (fob satisfaction). Before examination of hypothesis conducted, require to test the quality of data (validity and reliability) and classic assumption to ascertain to goodness-of-Jit regression model.Result of research show that data are valid and reliable, regression model are normal, not heteroskedastisy and not multikolinierifas. Pursuant to hypothesis test can be concluded that skilled variation do not haw an effect on to job satisfaction, while work autonomy and duty identity have an effect on positive and significant Keyword: work characteristic, skilled variation [of],  work autonomy duty identity, job satisfaction.